1999
DOI: 10.1103/physrevlett.82.5156
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Dissociative Adsorption of Methane onPt{110}(1×2)

Abstract: An exhaustive molecular beam study of methane dissociation on Pt͕110͖ ͑1 3 2͒ provides a new data base for modeling this process. Major new features include a sharp rise in dissociative sticking probability, s 0 , with increasing translational energy, E t , corresponding to a barrier of 238 meV, a dramatic increase in s 0 at higher E t with increasing vibrational energy, and a significant rise in s 0 as E t is lowered below ϳ100 meV. It is concluded that the low energy process is a distinctive steeringassisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 33 publications
(51 reference statements)
2
41
0
Order By: Relevance
“…The chemisorption of methane on transition metal (TM) surface has been studied extensively in this past decades by experimentalists (see Refs. [3][4][5][6] and papers cited therein) and by theoreticians [7][8][9][10]. The development of modern theoretical surfaces sciences provides an opportunity to investigate surfaces and adsorbate structures on the atomic scale with useful applications in industrial technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The chemisorption of methane on transition metal (TM) surface has been studied extensively in this past decades by experimentalists (see Refs. [3][4][5][6] and papers cited therein) and by theoreticians [7][8][9][10]. The development of modern theoretical surfaces sciences provides an opportunity to investigate surfaces and adsorbate structures on the atomic scale with useful applications in industrial technologies.…”
Section: Introductionmentioning
confidence: 99%
“…1.͒ Molecular beam experiments in which the dissociation probability was measured as a function of translational energy have observed that the dissociation probability is enhanced by the normal incidence component of the incidence translational energy. [2][3][4][5][6][7][8][9][10][11][12] This suggests that the reaction occurs primarily through a direct dissociation mechanism at least for high translational kinetic energies. Some experiments have also observed that vibrationally hot CH 4 dissociates more readily than cold CH 4 , with the energy in the internal vibrations being about as effective as the translational energy in inducing dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Some experiments have also observed that vibrationally hot CH 4 dissociates more readily than cold CH 4 , with the energy in the internal vibrations being about as effective as the translational energy in inducing dissociation. [2][3][4][7][8][9][10]13 A molecular beam experiment with laser excitation of the 3 mode did succeed in measuring a strong enhancement of the dissociation on a Ni͑100͒ surface. However, this enhancement was still much too low to account for the vibrational activation observed in previous studies and indicated that other vibrationally excited modes contribute significantly to the reactivity of thermal samples.…”
Section: Introductionmentioning
confidence: 99%
“…For H 2 -Pd(1 1 1) [9] and for H 2 and D 2 on V(1 1 1) [10] dissociation has been found to be strongly influenced by molecular rotation. More recently King and coworker [11] showed the existence of a distinctive steering assisted direct adsorption pathway for CH 4 on Pt(1 1 0)(1 Â 2) and Gee et al [12] discussed the role of steering in the dissociative adsorption of hydrogen on Pt(5 3 3). Although it has been demonstrated theoretically to be significant [7], the influence and signature of steering have not been established in non-dissociative, molecular adsorption (trapping).…”
mentioning
confidence: 99%